2021
DOI: 10.3390/biomedicines9060641
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bifidobacterium bifidum G9-1 Has a Preventive Effect on the Acceleration of Colonic Permeability and M1 Macrophage Population in Maternally Separated Rats

Abstract: Although probiotics may be useful for the treatment of irritable bowel syndrome (IBS), it is unclear how probiotics play a role in colonic mucosal integrity and immunity. Here, we aimed to investigate the effect of Bifidobacterium bifidum G9-1 (BBG9-1) on colonic mucosal integrity and macrophage behavior in rats subjected to maternal separation (MS) as a model of IBS. MS pups were individually separated from their mother rats, and a proportion of the MS rats were orally administered BBG9-1. The colonic mucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Preclinical research on targeted microbiome alterations is shown in Table 5 [ 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 ]. The range of these studies presages where Microbiome First Medicine is headed.…”
Section: Probiotics Prebiotics and Targeted Rebiosis: Clinical And Preclinical Examplesmentioning
confidence: 99%
“…Preclinical research on targeted microbiome alterations is shown in Table 5 [ 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 ]. The range of these studies presages where Microbiome First Medicine is headed.…”
Section: Probiotics Prebiotics and Targeted Rebiosis: Clinical And Preclinical Examplesmentioning
confidence: 99%
“…Relying on the precise regulation of the targeting properties of engineered bacteria, specific release of drugs at the tumor site can be achieved, which is beneficial to reduce the occurrence of adverse reactions related to immunotherapy. Besides, plenty of commensal probiotics such as Lactic acid bacteria, has exhibited benefits for the prevention of colitis and moderation of diarrhea, indicating that it is a promising choice to employ engineered probiotics to alleviate some adverse reactions (130).…”
Section: Perspectives and Prospectsmentioning
confidence: 99%
“…The era has passed in which the microbiome could simply be ignored in the practice of medicine. [184][185][186][187][188][189][190][191][192][193][194][195].…”
Section: Probiotics Prebiotics and Targeted Rebiosis: Clinical And Preclinical Examplesmentioning
confidence: 99%
“…Conversely, attempts at systems biology fixes while the microbiome remains in dysbiosis are questionable and are unlikely to produce permanent cures. (rat) [195] of the colonic mucosal problems as seen with irritated bowel; M1-macrophage driven inflammation effects. There were reduced numbers of M1 macrophages with increased CD-80 positive cells; reduced inflammatory cytokine production; the probiotic administration protected and stabilized the colonic mucosa…”
Section: Probiotics Prebiotics and Targeted Rebiosis: Clinical And Preclinical Examplesmentioning
confidence: 99%